European foreign conflict reporting a comparative analysis of public news providers - Heywood, Emma (Media, war and security, 2017)
This book explains that not only do hierarchies in news values exist in foreign conflict reporting but that they are never arbitrary and can be explained, in part, by the structure of the broadcasters and by events occurring within, or associated with, the reporting country, resulting in nationally differentiated perceptions of conflict throughout the world.